2018
DOI: 10.1002/ajpa.23699
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic features of scurvy in human skeletal remains: A literature synthesis and diagnostic guide

Abstract: The past two decades have seen a proliferation in bioarchaeological literature on the identification of scurvy, a disease caused by chronic vitamin C deficiency, in ancient human remains. This condition is one of the few nutritional deficiencies that can result in diagnostic osseous lesions. Scurvy is associated with low dietary diversity and its identification in human skeletal remains can provide important contextual information on subsistence strategy, resource allocation, and human‐environmental interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 81 publications
1
101
0
7
Order By: Relevance
“…Table lists the skeletal changes typically associated with treponemal infection and their diagnostic weight, expressed as consistent with treponemal infection, strongly indicative of treponemal infection, and pathognomonic. Weighted diagnostic systems have been advanced for other conditions (e.g., scurvy; see Brickley & Ives, ; Snoddy et al, ). The observations in Table form the basis for the suggested approach to recording the presence (and absence) of treponemal disease (a recommended recording form for keying an investigator into these alterations is included in Supporting Information).…”
Section: Paleopathologymentioning
confidence: 99%
“…Table lists the skeletal changes typically associated with treponemal infection and their diagnostic weight, expressed as consistent with treponemal infection, strongly indicative of treponemal infection, and pathognomonic. Weighted diagnostic systems have been advanced for other conditions (e.g., scurvy; see Brickley & Ives, ; Snoddy et al, ). The observations in Table form the basis for the suggested approach to recording the presence (and absence) of treponemal disease (a recommended recording form for keying an investigator into these alterations is included in Supporting Information).…”
Section: Paleopathologymentioning
confidence: 99%
“…To deal with this issue, a combination of lesions in different cranial and postcranial skeletal locations was proposed as a more reliable diagnosis method (Brickley et al, 2016;Brickley & Ives, 2008;Brown & Ortner, 2011;Klaus, 2014;Snoddy et al, 2018). In this paper, we followed the diagnosis method proposed by Brickley et al (2016), in which porosity at sites of blood vessels in cranial bones, hyperostosis, and/or periosteal new bone formation in the cranial bones and periosteal new bone formation in long bones is analysed to obtain a "probable," "possible," or "insufficient evidence" diagnosis of scurvy.…”
Section: Palaeopathological Analyses and Differential Diagnosismentioning
confidence: 99%
“…Although the symptoms of osteoporosis can already be seen in the skeletons of ancient human beings [8] and the first clinical descriptions appeared in the XIX century, we are still enriching our knowledge about the aetiology of the disease, the cellular mechanisms that govern it, and effective methods of treatment and prevention. Currently available therapeutic interventions in osteoporosis include calcium and vitamin D supplementation, as well as novel antiresorptive drugs such as ibandronate and denosumab.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms linking the diet and bone metabolism have not been fully elucidated. One plausible explanation is the putative buffering effect of acids derived from vegetables and fruits [8,9]. Moreover, numerous epidemiological studies suggested the importance of micronutrients such as ascorbic acid (vitamin C, VC) in protection against bone loss, not only due to their buffering effects [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation